Childfree Phenomenon in Indonesia - Sitti Muliya Rizka; Taat Kurnita Yeniningsih; Mutmainnah Mutmainnah; Yuhasriati Yuhasriati (Proceedings of AICS - Social Sciences, 2021)
Childfree is different from childless; Parents who decide to be childfree are those whochoose not to have children even though they have good economic and biologicaladequacy. While childless usually refers to those who want to become parents butcannot because of certain biological reasons. Being a parent requires careful preparation.The childfree phenomenon is developing in Indonesia. This phenomenon began to bediscussed in the midst of the general public and caused many pros and cons in societyregarding the freedom to have children. Based on data released by the World Bank, thetrend of birth rate in Indonesia continues to decline, even in 2019 the crude birth rateper 1,000 population issued by the BPS where there is a decrease in the populationgrowth rate. The benefits of the decision without children can be optimal only if adoptedby a small number of people. This is because each profit tends to decrease as thenumber of people using the same strategy increases.Keywords: Childfree, marriage, reason of childfree